26 Temporal change in the use of sodium glucose co-transporter 2 inhibitors. (30th September 2020) - Offiah, G; O'Connor, C; Khan, B; Moore, D
Abstract : Introduction: Diabetes mellitus (DM) is a major risk factor for cardiovascular disease (CVD). The EMPA-Reg study showed sodium glucose co-transporter 2 (SGLT2) inhibitors reduce the risk of death by 38% compared to placebo in diabetic patients with established CVD. These drugs have emerged as a major treatment option to reduce cardiovascular mortality as well as hospitalisation due to heart failure. The recent European Society of Cardiology (ESC) guidelines for DM has highlighted as a class I recommendation, the use of SGLT2 inhibitors as first line therapy in diabetics with established CVD or at high risk of CVD. This audit aims to determine whether the prescribing practices of SGLT2 inhibitors was influenced by the emergence of cardiovascular prevention data amongst patients with type 2 DM. Methods: Retrospective cohort analysis was performed on all patients admitted to the coronary care unit (CCU) between January 2011 and September 2019. A review of the electronic health records of patients with new or established type 2 DM, who had been admitted with acute coronary syndrome (ACS) or heart failure (HF) as their primary diagnosis code was performed. Discharge prescriptions were analysed to determine which patients had been prescribed a SGLT2 inhibitor. The admission creatinine and estimated glomerular filtration rate (eGFR) for all patients were recorded. eGFR ≥60 was used as the eligibility threshold for initiation of treatment with SGLT2 inhibitor as per summary of product characteristics. This data was analysed to determine whether there was a temporal change in prescriptions of this drug class. Statistical analysis was performed using standard Bayesain statistics. Results: There were 6870 patients admitted to the CCU between January 2011 and September 2019. 1054 patients had a diagnosis of type 2 DM and were admitted with ACS or HF. 77 patients were excluded from the study due to incomplete data. Thus, 977 patients were included in the final data set for analysis. There were 54 newly diagnosed diabetics and 923 with established type 2 DM. 865 patients were admitted with ACS and 112 patients with HF. The ratio of male to female was 2.6:1. The mean age of the patient cohort was 65. There was a total of 40 patients prescribed SGLT2 inhibitors. Prior to the EMPA-Reg study in 2015, there were 4 of 387 eligible patients prescribed SGLT2 inhibitors, compared to 36 of 221 eligible patients thereafter. Chi-square statistic 45.1429 (p <0.00001). Temporal analysis from 2015 to 2019 showed increase in use from 5.5% to 20.5% (figure 1 ). Conclusion: There was a statistically significant increase in the use of SGLT2 inhibitors since the EMPA-Reg study. Recent published data on the benefits this drug class confers on HF management further strengthens the evidence for this change in practice. The new ESC guidelines were published in September 2019, which we suspect will result in even more widespread use of these drugs.